Implementation of lightweight intrusion detection model for security of smart green house and vertical farm - Jun-Ho Huh (International Journal of Distributed Sensor Networks)
With the current global food production capability, it is not difficult to anticipate that there will be a global food shortage when the world population grows beyond 10 billion by the end of the 21st century. Many projects are in motion to deal with this problem and some of them are considered to be quite feasible. Development and implementation of smart green houses and vertical farms are two major solutions for the expected crisis, but as other ICT-based systems, their security problems must be dealt with. Nevertheless, current network forensics is still unable to fully monitor and analyze computer network traffic to gather the evidences of malicious attacks or intrusions. Although major companies and government agencies have introduced various types of high-speed IDS into their networks, smaller firms or private organizations are unable to do so because of the cost involved. The lightweight IDS proposed in this study can be a suitable solution as this system can be operated with a common PC and peripherals. This system also underwent a test bed experiment and proved its efficiency. Jpcap library was used to capture transport packets which were then classified using typical communications protocols. The packet headers were subjected to analysis and the results were stored in database for later applications.